Miðmætisspeglanir á Íslandi : árangur og ábendingar - Þóra Sif Ólafsdóttir; Gunnar Guðmundsson; Jóhannes Björnsson; Tómas Guðbjartsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) INTRODUCTION: Mediastinoscopy is an important tool for staging lung cancer and evaluating mediastinal pathology. The objective of this retrospective study was to investigate the indications and safety of mediastinoscopy in a well defined cohort of patients. MATERIAL AND METHODS: All patients that underwent mediastinoscopy in Iceland between 1983-2007 were included. Clinical information was obtained from patient charts and pathology reports rewied. The study-period was divided into 5-year periods for comparison. RESULTS: Altogether 278 operations were performed but in 17 cases data was missing, leaving 261 patients for analysis (mean age 59 yrs, range 11-89, 159 males). A steady increase was seen in the number of operations, or from 16 to 85 during the first and last periods, respectively (p<0.01). Staging of lung cancer (61,3%), evaluation of mediastinal tumors (24,5%), and suspected sarcoidosis (8,8%) were the most common indications. Mean operating time was 30 minutes (range 10-320) and median hospital stay 1 day (range 0,5-26). The most common histological diagnosis were nonspecific changes (33,6%), lung cancer (23,8%) and sarcoidosis (12,7%). Seven patients (2.7%) had complications; including 4 (1.5%) with hoarsness due to left recurrent nerve injury, one (0,3%) with pneumothorax and two with >500 ml hemorrhage (1.1%). There were two operative deaths (<30 days), one due to major intraoperative bleeding. CONCLUSIONS: The number of mediastinoscopies is increasing in Iceland, especially as a part of lung cancer staging. Mediastinoscopy is a safe procedure with low mortality and morbidity, where a specific diagnosis is obtained in most cases. Inngangur: Þegar nálgast þarf sýni úr miðmæti, til dæmis við stigun lungnakrabbameins eða við greiningu æxla af óþekktum uppruna, er miðmætisspeglun (mediastinoscopy) kjörrannsókn. Ekki liggja fyrir upplýsingar um ábendingar eða árangur þessara aðgerða ...